2013
DOI: 10.1007/s00204-013-1090-9
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic metabolizing enzyme activities in cells used for testing skin sensitization in vitro

Abstract: For ethical and regulatory reasons, in vitro tests for scoring potential toxicities of cosmetics are essential. A test strategy for investigating potential skin sensitization using two human keratinocytic and two human dendritic cell lines has been developed (Mehling et al. Arch Toxicol 86:1273–1295, 2012). Since prohaptens may be metabolically activated in the skin, information on xenobiotic metabolizing enzyme (XME) activities in these cell lines is of high interest. In this study, XME activity assays, monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Diethylenetriamine and resorcinol are putative pro-haptens. They are not detectable in the cell-free DPRA and may not be activated in the cellular assays due to a limited metabolic capacity (Fabian et al, 2013;Oesch et al, 2014). Benzoyl peroxide was strongly positive in the DPRA but negative in the KeratinoSens™ and h-CLAT.…”
Section: False Negative and False Positivesmentioning
confidence: 98%
See 1 more Smart Citation
“…Diethylenetriamine and resorcinol are putative pro-haptens. They are not detectable in the cell-free DPRA and may not be activated in the cellular assays due to a limited metabolic capacity (Fabian et al, 2013;Oesch et al, 2014). Benzoyl peroxide was strongly positive in the DPRA but negative in the KeratinoSens™ and h-CLAT.…”
Section: False Negative and False Positivesmentioning
confidence: 98%
“…This can be explained by the fact, that some members of this group might require enzymatic activation, which is absent in the in chemico assay. The cell-based test methods also have only limited metabolic capacities (Oesch et al, 2014;Fabian et al, 2013) and thus have limitations in detecting putative pro-haptens.…”
Section: Mechanistic Domainsmentioning
confidence: 99%
“…In most of these cases, sensitizers lacking electrophilic moieties were transformed to quinones, quinone imines or quinone methides as reactive intermediates, suggesting autoxidation. 31 The m/z values indicate that the reactive intermediates formed covalent bonds with the peptide following Michael additions (i.e., for 3, 4, 5, 6,9,10,11,12,13,16,17). As an example, the oxidative activation of the pre-hapten hydroquinone (6) to the highly electrophilic Michael acceptor para-benzoquinone and the molecular structure of its corresponding adduct is shown in Figure 3.…”
Section: A4mentioning
confidence: 99%
“…Dressler and Appelqvist (2006) tentatively identified NAT1 to mediate in the rat skin the acetylation of para-aminophenol. NAT1 activity is not stable leading to quite variable results (Fabian et al 2013). …”
Section: Xenobiotica-metabolizing Enzymes In the Rat Skinmentioning
confidence: 99%
“…Fabian et al (2013) reported that in U937 und THP-1 (dendritic cell lines from the German Collection of Microorganisms and Cell Cultures) and in the keratinocytic cell lines LuSens (developed by BASF SE) and KeratinoSens ® (developed by Givaudan) EROD, PROD and BROD activities were below the LOD.…”
Section: Xenobiotica-metabolizing Enzymes In the Human Skin Includingmentioning
confidence: 99%